DIVERSIFIKASI PENDIDIKAN PESANTREN: TANTANGAN DAN SOLUSI - Fuaduddin TM (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractPesantren has been recognized aas educational institution that has played a role in civilizing and enlightening the life of Indonesian people. In one side, pesantren institution potentially can give society education service. But in another side, there are many of alumni of pesantren who are difficult either to continue their study to higher education or to seek job especially in the public sector or other formal sectors. This condition is one of modern phenomenda which strictly demands differentiation, specialization and professionalization. This paper talks about the development of various orientation od pesantren education system, the challenges faced, and strategic actions should be done.